Anti-platelet therapy holds promises in treating adenomyosis: experimental evidence. Issue 1 (December 2016) - Zhu, Bo; Chen, Yumei; Shen, Xiaolu; Liu, Xishi; Guo, Sun-Wei
Abstract Background Recently emerging evidence indicates that endometriotic lesions are wounds undergoing repeated tissue injury and repair (ReTIAR), and platelets induce epithelial-mesenchymal transition (EMT), fibroblast-to-myofibroblast transdifferentiation (FMT), leading ultimately to fibrosis. Due to the commonality of cyclic bleeding as in endometriosis, adenomyotic lesions are also wounds that undergo ReTIAR, and we have recently provided evidence corroborating platelet-induced EMT, FMT and fibrogenesis in adenomyosis. This study sought to evaluate the effect of antiplatelet therapy in a mouse model of adenomyosis. Methods Adenomyosis was induced in 57 female ICR mice with neonatal dosing of tamoxifen, while another 12 (group C) were dosed with solvent only, serving as a blank control. Starting from 4 weeks after birth, hotplate test was administrated to all mice every 4 weeks. At the 16th week, all mice with induced adenomyosis were randomly divided into 6 groups: untreated, low- and high-dose Ozagrel, low- and high-dose anti-mouse GPIbα polyclonal IgG antibody to deplete platelets, and isotype-matched inert IgG non-immune antibody. Group C received no treatment. After 3 weeks of treatment, they were hotplate tested again, their uterine horns and brains were harvested, and a blood sample was taken to measure the plasma corticosterone level by ELISA. The left uterine horn was used for immunohistochemistry analysis. The brainstem nucleus raphe magnus (NRM) sections were subjected to immunofluorescence staining for GAD65. The depth of myometrial infiltration and uterine contractility were evaluated. Results We found that both Ozagrel treatment and platelet depletion dose-dependently suppressed myometrial infiltration, improved generalized hyperalgesia, reduced uterine contractility, and lowered plasma corticosterone levels, improved the expression of some proteins known to be involved in adenomyosis and slowed down the process of fibrogenesis. It also elevated the number of GAD65-expressing neurons in the brainstem NRM, possibly boosting the GABAergic inhibition of pain due to adenomyosis. Conclusion This study further provides evidence that platelets play important roles in the development of adenomyosis. Anti-platelet treatment is efficacious in suppression of myometrial infiltration, improving generalized hyperalgesia, reducing uterine hyperactivity and systemic corticosterone levels. Collectively, these results demonstrate that anti-platelet therapy seems to be promising for treating adenomyosis.